A Case of Reactive Arthritis Associated With Lymphogranuloma Venereum Infection in a Woman. Issue 9 (September 2016) - Foschi, Claudio; Banzola, Nicoletta; Gaspari, Valeria; D'Antuono, Antonietta; Cevenini, Roberto; Marangoni, Antonella
Abstract : Abstract: We report the first case of reactive arthritis associated with lymphogranuloma venereum (LGV) in an Italian human immunodeficiency virus–negative woman with urogenital and rectal Chlamydia trachomatis L2 serovar infection. The LGV-associated arthritis has to be considered even when classic symptoms of arthritis are missing and in case of asymptomatic or cryptic LGV localizations. Abstract : A case of reactive arthritis secondary to lymphogranuloma venereum urogenital and anorectal infection in a human immunodeficiency virus–negative woman was reported.